How has the Ascend programme contributed to strengthening health systems for sustainable country-driven neglected tropical disease programming?. (21st September 2022) - Rowan, Sinead; Amodu-Agbi, Perpetua; Weil, Olivier; Northway, Diane; Ene, Nkem; Gwom, Anita; Pavluck, Alexandre
Abstract: The Ascend West and Central Africa programme, a UK aid-funded programme, was implemented across 12 countries. The programme focused on strengthening national health systems for sustainable neglected tropical disease (NTD) control and elimination. This commentary presents how Ascend's approach contributed to developing country-driven sustainable systems for NTDs and offers learnings to inform future sustainable NTD programming.